HEATER PROBE TREATMENT IN THE ACTIVE UPPER GASTROINTESTINAL TRACT BLEEDING - Yaşar ACAR; M. Enver DOLAR; Tevfik Ali KÜÇÜKBAŞ; Uğur YILMAZ; Çağlar BAYSAL; Bülent YILDIRIM; Burhan ŞAHİN (Turkish Journal of Gastroenterology, 2020)
-